Improving bicycle sharing operations: A multi-criteria decision-making approach. (15th May 2021) - Liu, Aijun; Wang, Ruiyao; Fowler, John; Ji, Xiaohui
Abstract: Bicycle sharing is quickly becoming popular because it is environmentally friendly and offers convenience to customers. Determining how to improve the service level and customer satisfaction are the keys to a successful bicycle sharing business in today's fiercely competitive market and are also the keys to achieving a sustainable operation. In this paper, following a hierarchical structure, five main factors related to the bicycle sharing operations are identified: (1) convenience and flexibility, (2) operation service, (3) economic cost, (4) design and layout and (5) management specification. Eighteen sub factors are then derived. To determine the significant factors affecting bicycle sharing operations, the Multi-Criteria Decision-Making (MCDM) approach based on Interval Type-2 Fuzzy Sets (IT2FSs), Decision Making Trial and Evaluation Laboratory Model (DEMATEL) and the Analytic Network Process (ANP) are proposed. First, IT2FSs and fuzzy DEMATEL are integrated to analyze the complex relationships among the various factors. DEMATEL is then integrated with ANP to rank the importance of these factors. Results are compared with those of other state-of-the-art MCDM methods. It is concluded that convenience and flexibility, rationality of the layout, and economic cost are the three most important factors impacting the bicycle sharing business model. Based on the findings, theoretical guidance for the development of bicycle sharing operations is provided. Graphical abstract: Image 1 Highlights: Considering attribute relationships and weights, a supermatrix is proposed. Economic cost is crucial to the operation and management of bicycle-sharing. Prioritize connectivity between bicycle-sharing and destinations for flexibility. Preferential rent is an effective method to improve the service level.